PENGARUH KOMITMEN ORGANISASIONAL, KEPEMIMPINAN, MOTIVASI DAN PEMBERDAYAAN KERJA TERHADAP KINERJA (Studi Pada Hotel Di Yogyakarta) - Winarno, Winarno (Jurnal Riset Akuntansi dan Keuangan, 2009)
This reseqrch examined effect of Organizational commitment, Leadership, motivation and work empowerrnent on performance. Data was collected from supervisor/managerat hotel in Yogtakarta. Complete data were obtained for 100 karyawan dyads. Every item research wqs measured by yalidity and reliability test. The hypathesis was analyzed by multiple regression technique. F-test examines the simultaneously in/luence of independent variable on dependent yarinble, and t-test examines the partial inJluence with level of significance 5ok.Kqt word : work climate, leadership, motivation, empowelment and performance